Complement Activation Is Associated With Mortality in Patients With Necrotizing Soft-Tissue Infections—A Prospective Observational Study - Kristensen, Markus Korsholm; Hansen, Marco Bo; Madsen, Martin Bruun; Hansen, Cecilie Bo; Pilely, Katrine; Hyldegaard, Ole; Garred, Peter (Frontiers in Immunology, 2020)
Aim: We assessed whether different complement factors and complement activation products were associated with poor outcome in patients with necrotizing soft-tissue infection (NSTI). Methods: We conducted a prospective, observational study in an intensive care unit where treatment of NSTI is centralized at a national level. In 135 NSTI patients and 65 control patients, admission levels of MASP-1, MASP-2, MASP-3, C4, C3, complement activation products C4c, C3bc and terminal complement complex (TCC) were assessed. Results: The 90-day mortality was 23%. In a Cox regression model adjusted for sex, and SAPS II, a higher than median MASP-1 (HR 0.378, CI 95% [0.164– 0.872], p = 0.0226) and C4 (HR 0.162, 95% CI [0.060– 0.438], p = 0.0003 ), C4c/C4 ratio (HR 2.290 95% CI [1.078– 4.867], p = 0.0312), C3bc (HR 2.664 95% CI [1.195– 5.938], p = 0.0166) and C3bc/C3 ratio (HR 4.041 95% CI [1.673– 9.758], p = 0.0019) were associated with 90-day mortality, while MASP-2, C4c, C3 and TCC were not. C4 had the highest ROC-AUC (0.748, [95% CI 0.649–0.847]), which was comparable to the AUC for SOFA score (0.753, [95% CI 0.649–0.857]), and SAPS II [0.862 95% CI 0.795–0.929]). Conclusion: In adjusted analyses, high admission levels of C4c/C4 ratio, C3bc, and the C3bc/C3 ratio were significantly associated with a higher risk of death after 90 days while high admission levels of MASP-1 and C4 were associated with lower risk. In this cohort, these variables are better predictors of mortality in NSTI than C-reactive protein and Procalcitonin. C4’s ability to predict mortality was comparable to the well-established scoring systems SAPS score II and SOFA on day 1.